تأثير المستخلص المائي لأوراق نبات الدفلة في الفئران البيضاء المستحدث فيها داء السكري - فاضل, هيام; دريوس, محمد; يوسف, خلود (Latakia University Journal -Biological Sciences Series, 2016)
تمّ إجراء البحث بهدف دراسة تأثير المستخلص المائي لأوراق نبات الدفلة في مستوى سكر الدم والكوليسترول الكلي والغليسيريدات الثلاثية للفئران المستحدث فيها داء السكري . وبينت النتائج مايلي:ارتفاع معنوي في تركيز كل من الغلوكوز والكوليسترول والغليسيريدات الثلاثية في مصل دم الفئران المستحدث فيها داء السكري ،وانخفاض الوزن بالمقارنة مع الشاهدة.أدى الحقن بالمستخلص المائي لأوراق نبات الدفلة بجرعة 200ملغ/كغ من وزن الفأر ولمدة عشرة أيام الى انخفاض معنوي بتركيز الغلوكوز ومعدل الكوليسترول الكلي والغليسيريدات الثلاثية ،كما عاد الوزن إلى ما كان عليه قبل الحقن.This research has done in aiming for the effect of extract of Nerium oleander plant in the level of blood sugar and total glucose , triple alglesiredat and total cholesterol on created albino mouse which has got diabetes. The results showed the following:- A Significant increase in the concentration on bothglucose, triple alglesiredat and cholesterol through a serum in the blood of created albino mouse which has got diabetes, while the weight decreases comparing to the control.- The injection of Aqueous extract led oleander leaves plant with dose of 200 mg / kg of mouse weight for a period of ten days to a significant decrease of concentration on glucose ,the rate of total cholesterol and triple alglesiredat, in addition to, the weight has returned to what it was before the injection.